A Grassland Bird's Changing World - Ogborn, Callie; Hallaq, Tom (Kansas State University, 2017)
Prairies are characterized by highly variable climate, yet we lack the theoretical knowledge to predict whether adaption to such conditions offers organisms greater resilience to additional change, or whether they already experience conditions near the limits of their physiological capabilities. This study capitalizes upon a 28-yr dataset of avian abundances and the infrastructure and experimental manipulations made possible by the Long Term Ecological Research (LTER) program at the Konza Prairie in NE Kansas. It integrates the insights from long-term data with detailed, mechanistic, individual-level data from a marked population of declining songbirds to predict biotic responses to future environmental conditions.
Keywords: Boyle, Alice